A highly localized high‐precipitation event over Corsica. (18th May 2016) - Scheffknecht, P.; Richard, E.; Lambert, D.
Abstract : In the framework of the Hydrological Cycle of the Mediterranean Experiment (HyMeX), the high precipitation event (HPE) of 23 October 2012 is investigated. In the morning, a highly localized convective system developed over the southeast of Corsica, close to Porto‐Vecchio. Its precipitation maximum is estimated at over 100 mm within 6 h. The Meso‐NH model is used with a horizontal grid spacing of 2.5 km to simulate the HPE. Different input datasets and starting times are used to assess the predictability of the event and the large spread of this initial condition ensemble indicates low predictability. Among the nine ensemble members only one captures the timing and location of the event. When the horizontal grid spacing is reduced to 500 m, precipitation is more widespread, maximum values are lower, and individual convective cells are smaller. Random perturbations to model physics are used to obtain a second ensemble, which shows less spread than the initial condition ensemble. The HPE over Porto‐Vecchio is present in all members of the physics ensemble with varying intensity while precipitation away from orography is more sensitive. Flattening the Corsican orography removes the HPE while blocking the cold northerly inflow into the Mediterranean basin increases its duration and intensity. From the analyses and simulations it is shown that the HPE of 23 October 2012 was located over a convergence line resulting from flow splitting and lee‐side convergence of the northerly boundary‐layer flow impinging the Corsican mountains. Moist air located east of the island was fed into this convergence line by northerly low‐level winds and southeasterly winds aloft advected the cells inland along the stationary convergence line, allowing large precipitation accumulations over a relatively small area.